2021
DOI: 10.1111/ibi.12968
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic space use of Andalusian rice fields by Lesser Black‐backed Gulls (Larus fuscus) is driven by flooding pattern

Abstract: Research on the space use and behaviour of waterbirds yields important insights on human-wildlife interactions of ecological and societal importance under global change. The extent to which dynamic (within-season) changes in anthropogenic landscapes affect these interactions is poorly understood. Lesser Black-backed Gulls Larus fuscus are prominent bio-vectors of biological, synthetic and inorganic materials and have exhibited large increases in abundance in parts of southern Europe in recent decades. We combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Kleyheeg, et al [ 39 ] found that seed survival increased significantly with forced activity in ducks. LBBGs spend long periods of the day inactive, roosting in rice fields or neighbouring habitats [ 40 ], so our experiment may reflect field conditions quite well.…”
Section: Discussionmentioning
confidence: 99%
“…Kleyheeg, et al [ 39 ] found that seed survival increased significantly with forced activity in ducks. LBBGs spend long periods of the day inactive, roosting in rice fields or neighbouring habitats [ 40 ], so our experiment may reflect field conditions quite well.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial methods, mainly using nitrogen and phosphorus application, are employed for fertilization in these agroecosystems, excluding the use of manure (Campos et al, 2010). These paddy fields are a key node of high functional connectivity with other habitat types, including landfills (López-Calderón et al, 2023;Martín-Vélez et al, 2020a, 2020bvan Rees et al, 2021). The Montemarta-Cónica landfill is the largest integrated municipal solid waste treatment centre in Andalusia, managing >620,000 tons per year of waste, including organic matter, packaging, construction, biosanitary waste, and leachate.…”
Section: Model Species and Study Sitesmentioning
confidence: 99%
“…Study site selection was based on GPS tracking data and the use of O. Sacristán-Soriano et al habitat by birds (see (López-Calderón et al, 2023;Martín-Vélez et al, 2020b;van Rees et al, 2021).…”
Section: Model Species and Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased population growth and rapid urban development have brought new challenges to SWM in both developing [5][6][7] and developed countries [8][9][10]. In situ data collection and frequent field monitoring of environmental analysis are gradually replaced with newer and more efficient methods, such as remote sensing (RS) and Geographical Information System (GIS) techniques.…”
Section: Introductionmentioning
confidence: 99%